7                 env -> 'a;;
8         let unit (a : 'a) : 'a reader =
9                 fun e -> a;;
11                 fun e -> (fun v -> f v e) (u e);;
13 We've just beta-expanded the familiar `f (u e) e` into `(fun v -> f v
14 e) (u e)`, in order to factor out the parts where any Reader monad is
15 being supplied as an argument to another function, as illustrated in
16 the `bind` function in the following example. Then if we want instead
18 M.unit and M.bind, here's how we do it:
22         (* We're not giving valid OCaml code, but rather something
23          * that's conceptually easier to digest.
24          * How you really need to write this in OCaml is more circuitous...
25          * see http://lambda.jimpryor.net/code/tree_monadize.ml for some details. *)
27         type ('a, M) readerT =
28                 env -> 'a M;;
29         (* this is just an 'a M reader; but don't rely on that pattern to generalize *)
31         let unit (a : 'a) : ('a, M) readerT =
32                 fun e -> M.unit a;;
34         let bind (u : ('a, M) readerT) (f : 'a -> ('b, M) readerT) : ('b, M) readerT =
35                 fun e -> M.bind (u e) (fun v -> f v e);;
37 Notice the key differences: where before we just returned `a`, now we
38 instead return `M.unit a`. Where before we just supplied value `u e`
39 of type `'a reader` as an argument to a function, now we instead
40 `M.bind` the `'a reader` to that function. Notice also the differences
41 in the types.
43 What is the relation between Reader and ReaderT? Well, suppose you started with the Identity monad:
45         type 'a identity = 'a;;
46         let unit (a : 'a) : 'a = a;;
47         let bind (u : 'a) (f : 'a -> 'b) : 'b = f u;;
51 The relations between the State monad and the StateT monadic transformer are parallel:
55         type 'a state =
56                 store -> ('a * store);;
58         let unit (a : 'a) : 'a state =
59                 fun s -> (a, s);;
61         let bind (u : 'a state) (f : 'a -> 'b state) : 'b state =
62                 fun s -> (fun (a, s') -> f a s') (u s);;
64 We've used `(fun (a, s') -> f a s') (u s)` instead of the more familiar `let (a, s') = u s in f a s'` in order to factor out the part where a value of type `'a state` is supplied as an argument to a function. Now StateT will be:
68         type ('a, M) stateT =
69                 store -> ('a * store) M;;
70         (* notice this is not an 'a M state *)
72         let unit (a : 'a) : ('a, M) stateT =
73                 fun s -> M.unit (a, s);;
75         let bind (u : ('a, M) stateT) (f : 'a -> ('b, M) stateT) : ('b, M) stateT =
76                 fun s -> M.bind (u s) (fun (a, s') -> f a s');;
78 Do you see the pattern? Where ordinarily we'd return an `'a` value, now we instead return an `'a M` value. Where ordinarily we'd supply a `'a state` value as an argument to a function, now we instead `M.bind` it to that function.
80 Okay, now let's do the same thing for our Tree monad.
84         type 'a tree =
85                 Leaf of 'a | Node of ('a tree) * ('a tree);;
87         let unit (a: 'a) : 'a tree =
88                 Leaf a;;
90         let rec bind (u : 'a tree) (f : 'a -> 'b tree) : 'b tree =
91             match u with
92             | Leaf a -> f a;;
93             | Node (l, r) -> (fun l' r' -> Node (l', r')) (bind l f) (bind r f);;
96         (* NOTE THIS IS NOT YET WORKING --- STILL REFINING *)
98         type ('a, M) treeT =
99                 'a tree M;;
101         let unit (a: 'a) : ('a, M) tree =
102                 M.unit (Leaf a);;
104         let rec bind (u : ('a, M) tree) (f : 'a -> ('b, M) tree) : ('b, M) tree =
105             match u with
106             | Leaf a -> M.bind (f a) (fun b -> M.unit (Leaf b))
107             | Node (l, r) -> M.bind (bind l f) (fun l' ->
108                                                         M.bind (bind r f) (fun r' ->
109                                                                 M.unit (Node (l', r'));;